Recent Progress in Thermal Conversion of CO2 via Single‐Atom Site Catalysis. Issue 9 (15th June 2022) - Wang, Qishun; Zheng, Xiaobo; Wu, Jiabin; Wang, Yao; Wang, Dingsheng; Li, Yadong
Abstract : CO2 emission has been an international issue of great concern. Utilizing of CO2, especially converting it to value‐added products, is widely investigated, among which the thermal conversion of CO2 has enormous potential for industry. Researches on single‐atom site catalysis (SAC) have become increasingly systematic during the last years. High performance and distinctive selectivity that SAC exhibits attribute to the isolated structure a large extent. To understand the structure–performance relationship of SAC in CO2 activation, issues including substrate, active components, coordination, chemical structure, etc. are of the essence not only in academia but also in industry. However, it is far away from the vision that the synthetic procedure and reaction pathway are deeply comprehended, thereupon precise single‐atom sites with specific structure are constructed and elementary reactions are regulated at will. Still a lot of efforts are needed to this field. Herein, CO2 reduction reactions are reviewed according to the products, and then catalysts are introduced by the substrate. The promoter, stability, synthesis/regeneration, characterization, and theory calculation issue related to SAC and CO2 activation are comprehensively summarized and discussed. Looking back the progress, challenge and outlook of single‐atom site catalysis are also proposed. Abstract : Adopting single‐atom site catalysis (SAC) in thermal conversion of CO2 has enormous potential for industry. By summarization and discussion on promoter, stability, synthesis/regeneration, characterization, and theory calculation issue related to SAC and CO2 activation, the recent progress on CO2 reduction reactions is reviewed according to the products catalyzed by single‐atom site catalysts with a classification of the substrate.